L’Éducation nouvelle et l’idée de liberté : approche trialectique - Emilie Osmont (Éducation et Socialisation)
From a model of thinking based on a trialectic logic, this article proposes to study the conditions of existence of the link between freedom and education since the humanism of the Renaissance was defined as consubstantial. More specifically, referring to the paradigm of complexity, which is enriched by the contributions of trialectic logic, we study the relationship freedom / education on repositioning it in a complex network of influences in order to highlight the concepts third who successively governed it. If it is recognized that the New Education is not so "new", this work about freedom - figurehead of this movement - has the advantage of showing that, indeed, the idea of freedom carried by this movement is the product of past influences, while it is also a complex renegotiation of this legacy through the emergence of a new mediator concept that redefines the relationship between freedom and education.